New insight into DAVF pathology—Clues from meningeal immunity - Tu, Tianqi; Peng, Zhenghong; Song, Zihao; Ma, Yongjie; Zhang, Hongqi (Frontiers in Immunology, 2022)
In recent years, with the current accesses in techniques, studies have significantly advanced the knowledge of meningeal immunity, revealing that the central nervous system (CNS) border acts as immune landscape. The latest concept of meningeal immune system is a tertiary structure, which is a comprehensive overview of the meningeal immune system from macro to micro. We comprehensively reviewed recent advances of the meningeal immunity, particularly about the new understanding of the dural sinus and meningeal lymphatics. Moreover, based on the clues from the meningeal immunity, new insights were proposed into the dural arteriovenous fistula (DAVF) pathology, aiming to provide novel ideas for DAVF understanding.